Crack control in concrete walls through novel mixture design, full-scale testing, and finite element analysis. (30th March 2018) - Michael, Jacob; Smith, Scott H.; Durham, Stephan A.; Chorzepa, Mi Geum
Highlights: Novel mixtures including crystalline PRA showed excellent strength performance. Use of fibers showed acceptable workability during field placement. The mixture containing the PRA showed the lowest hydraulic conductivity. The novel mixtures resulted in a significant reduction in the heat of hydration. Greatest thermal strains will occur in the lower third of the wall. HoH has the greatest effect on cracking potential of cast-in-place walls. Abstract: The research evaluates novel concrete mixtures, including crystalline admixtures, coarse ground calcium carbonate, and macro/micro-fibers, for use in basement walls that satisfy the International Residential Code with a reduction in reinforcement. The experimental investigation proved the mixture exceeds the 28-day design strength within 7 days of age with excellent long-term strength gain. Addition of the crystalline permeability-reducing admixture was found to reduce the rapid chloride permeability and hydraulic conductivity. To validate the applicability of the respective mixtures, a nonlinear finite element analysis was developed to estimate thermal stresses and cracking at the basement walls when subjected to environmental loads and thermal gain from the heat of hydration. It is concluded through the experimental and numerical efforts that the novel mixtures are capable of mitigating thermal and early-age shrinkage cracks.